2008
DOI: 10.1016/j.chiabu.2007.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for paternal physical child abuse

Abstract: There is a need for interventions within the child welfare system that better promote family wellbeing by including fathers in services. Patterns linking paternal socio-demographic and psychosocial factors to psychological and physical child abuse varied as a function of paternal race/ethnicity, indicating that race/ethnic differences are among the important factors that intervention efforts should take into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
3
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 83 publications
(115 reference statements)
4
46
3
2
Order By: Relevance
“…In addition, only 25% of participants lived with both biological parents, indicating that fathers may not have been present in the daily lives of many of these children. This finding is consistent with a recent study that found no significant correlation between paternal employment and paternal child abuse (Lee, Guterman, & Lee, 2008). More research is needed to determine if fathers' employment status affects symptoms of child abuse survivors.…”
Section: Discussionsupporting
confidence: 94%
“…In addition, only 25% of participants lived with both biological parents, indicating that fathers may not have been present in the daily lives of many of these children. This finding is consistent with a recent study that found no significant correlation between paternal employment and paternal child abuse (Lee, Guterman, & Lee, 2008). More research is needed to determine if fathers' employment status affects symptoms of child abuse survivors.…”
Section: Discussionsupporting
confidence: 94%
“…However, prior studies of spanking that included fathers have generally examined predictors of fathers' spanking (Lee, Guterman, & Lee, 2008;Lee et al, 2011); fathers' spanking separately from mothers (Lee, Taylor, Altschul, & Rice, 2013;Prinzie et al, 2006); or did not examine the transactional nature of parent child interactions (Lee, Taylor, Altschul, & Rice, 2013). The current study is unique because the separate and simultaneous use of transactional models to examine fathers' and mothers' use of physical punishment permits us to identify whether fathers' use of spanking has any unique influence after accounting for mothers' spanking.…”
Section: Use Of Spankingmentioning
confidence: 85%
“…One possible reason for this may be the criminalization of spanking and the cultural stigma associated with physical aggression toward children in Scandinavian countries (Modig, 2009). In the US, spanking is often culturally accepted and common (Lee, Guterman & Lee, 2008) and may evolve into more severe violence (Straus & Stewart, 1999). …”
Section: Discussionmentioning
confidence: 99%